Paulicéia de ontem: as revistas ilustradas e o viver urbano nas primeiras décadas do século XX - Braglia, Nádia Christina (2011)
This study reflects about new forms of sociabilities, habits and tastes appeared in the city of São Paulo between beginning of twenty century and the 1920 decade. Analysis advertisements and personal announcements that acted as transmitter in newspapers and periodicals such as: Vida paulista, A lua, Vida Moderna e A Cigarra, that circulated in the city in beginning of decade of twenty century. The study deliniates the geography of new spaces localized in the Triangle and its around, such like and to beyond the central region, and what forms these new spaces of leisure and sociabilities were divulged and inserted mainly in the daily life of cream of Paulistan s society and what ways they built an imaginary idea about the city that they wished to become modern and civilized such as the European standard